Rats prefer mutual rewards in a prosocial choice task - Hernandez-Lallement, Julen; van Wingerden, Marijn; Marx, Christine; Srejic, Milan; Kalenscher, Tobias (Frontiers in Neuroscience, 2015)
Pro-sociality, i.e. the preference for outcomes that produce benefits for other individuals, is ubiquitous in humans. Recently, cross-species comparisons of social behavior have offered important new insights into the evolution of pro-sociality. Here, we present a rodent analog of the Pro-social Choice Task that controls strategic components, de-confounds other-regarding choice motives from the animals’ natural tendencies to maximize own food access and directly tests the effect of social context on choice allocation. We trained pairs of rats – an actor and a partner rat – in a double T-maze task where actors decided between two alternatives only differing in the reward delivered to the partner. The "own reward" choice yielded a reward only accessible to the actor whereas the "both reward" choice produced an additional reward for a partner (partner condition) or an inanimate toy (toy Condition), located in an adjacent compartment. We found that actors chose “both reward” at levels above chance and more often in the partner than in the toy condition. Moreover, we show that this choice pattern adapts to the current social context and that the observed behavior is stable over time.